Characteristics of Meningitis in Febrile Infants Aged ≤90 Days - Kyu Un Cho; Su Jeong You (Korean Child Neurology Society, 2021)
Purpose This study evaluated the clinical and laboratory characteristics of infants ≤90 days old with meningitis who presented to the hospital with a fever. We also investigated whether initial C-reactive protein levels and white blood cell counts were reliable predictors of bacterial meningitis. Methods The medical records of 1,151 infants aged ≤90 days who visited our hospital with a fever between October 2009 and October 2019 were retrospectively evaluated. Results Of the 1,151 patients, 274 (23.8%) had meningitis (bacterial, n=7; viral, n=206; pleocytosis in the cerebrospinal fluid, n=136). Thirty-seven viral meningitis patients (18.0%) had a positive polymerase chain reaction result without pleocytosis in the cerebrospinal fluid. The patients without pleocytosis were significantly younger. Among the patients with only pleocytosis, 46 had a urinary tract infection, 22 had other viral infections, and the etiology was unknown in 68. Among patients with urinary tract infections, infants without pleocytosis were younger than those with pleocytosis. Low white blood cell counts (<5,000/mm3) were more frequently found in bacterial meningitis patients (n=7) than in viral meningitis patients. Furthermore, there were normal C-reactive protein levels (42.9%) and no pleocytosis (20%) in some cases of bacterial meningitis. Conclusion Our findings show that meningitis is not uncommon among infants ≤90 days old who were brought to the hospital with complaints of fever. Furthermore, younger patients may not have cerebrospinal fluid pleocytosis, even if they have bacterial meningitis. Therefore, the patient's condition should be monitored closely and, if necessary, a re-examination should be considered.